2017
DOI: 10.1021/acs.jpclett.7b01856
|View full text |Cite
|
Sign up to set email alerts
|

UV–Vis Action Spectroscopy Reveals a Conformational Collapse in Hydrogen-Rich Dinucleotide Cation Radicals

Abstract: We report the generation of deoxyriboadenosine dinucleotide cation radicals by gas-phase electron transfer to dinucleotide dications and their noncovalent complexes with crown ether ligands. Stable dinucleotide cation radicals of a novel hydrogen-rich type were generated and characterized by tandem mass spectrometry and UV-vis photodissociation (UVPD) action spectroscopy. Electron structure theory analysis indicated that upon electron attachment the dinucleotide dications underwent a conformational collapse fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 35 publications
4
50
0
Order By: Relevance
“…In the next step, the cations are discharged by collisions with a gaseous electron donor, forming radicals that are analyzed by tandem mass spectrometry . While this approach worked well for nucleobases, the more complex oligonucleotide cation radicals formed by electron transfer underwent fast isomerizations by proton or hydrogen atom migrations between the nucleobases . To generate and characterize nucleoside radicals, which are the primary intermediates of relevance for the early stages of DNA damage, a different approach was needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the next step, the cations are discharged by collisions with a gaseous electron donor, forming radicals that are analyzed by tandem mass spectrometry . While this approach worked well for nucleobases, the more complex oligonucleotide cation radicals formed by electron transfer underwent fast isomerizations by proton or hydrogen atom migrations between the nucleobases . To generate and characterize nucleoside radicals, which are the primary intermediates of relevance for the early stages of DNA damage, a different approach was needed.…”
Section: Methodsmentioning
confidence: 99%
“…To generate a stable cation radical ( 2 +H) +. for action spectroscopy, we resorted to a previously developed technique that relies on electron‐transfer dissociation (ETD) of non‐covalent complexes with crown ethers, such as 2,3:11,12‐dibenzo‐18‐crown‐6‐ether (DBCE). The doubly charged complex, ( 2 +H+DBCE) 2+ , m / z 406.5, was formed readily by electrospray ionization and furnished abundant cation radicals ( 2 +H) +.…”
Section: Methodsmentioning
confidence: 99%
“…Ion action spectroscopy relies on photodissociation of mass-selected gas-phase ions whereby the wavelength-dependent photofragment ion intensities are used to reconstruct the absorption profile of the precursor ion. Several variants of action spectroscopies have been developed working in the infrared or UV–vis regions of the spectrum. Multiphoton infrared photodissociation spectroscopy has been the most popular technique for small ions, whereas its applications to strongly hydrogen bonded systems have faced difficulties with band assignment and spectral interpretation. , UV–vis spectroscopy utilizing valence electron excitation and single-photon dissociation largely avoids such issues and has been shown to provide structural information for larger biomolecular ions that show characteristic absorption bands, such as peptide and oligonucleotide cation radicals. …”
Section: Introductionmentioning
confidence: 99%
“…[9,10] While this approach worked well for nucleobases, the more complex oligonucleotide cation radicals formed by electron transfer underwent fast isomeriza-tions by proton or hydrogen atom migrations between the nucleobases. [11] To generate and characterize nucleoside radicals, which are the primary intermediates of relevance for the early stages of DNA damage, a different approach was needed.…”
mentioning
confidence: 99%
“…Adenosine conjugates 1 + and 2 + were synthesized as shown in Scheme S1 (Supporting Information), and characterized by high-resolution and collision-induced dissociation tandem mass spectrometry, CID-MS 2 , as described in the Suporting Information (Table S1, Figures S1 a,b and S2 a,b). We found that electron transfer to doubly charged (2 + H) 2+ (m/z 226.5) resulted in a near complete dissociation (Figure 1 a) C for action spectroscopy, we resorted to a previously developed technique [11] that relies on electron-transfer dissociation (ETD) [13] of non-covalent complexes with crown ethers, such as 2,3:11,12-dibenzo-18-crown-6-ether (DBCE). The doubly charged complex, (2 + H + DBCE) 2+ , m/z 406.5, was formed readily by electrospray ionization and furnished abundant cation radicals (2 + H) + C (m/z 453) by reduction and loss of DBCE upon ETD (Figure 1 b).…”
mentioning
confidence: 99%